The The Effect of Inside Outside Circle Learning Model on Students' Critical Thinking Skills on Colloid Material - Chintia Rhamandica; Faridatul Umami (Universitas Lampung, 2025)
This study focuses on educational resources in chemistry that emphasize colloids, a topic that many students find difficult to understand. The difficulties mainly stem from the highly theoretical nature of colloids, which requires hands-on experience and the ability to think critically. Despite this, teachers frequently rely on conventional methods during their lessons. One strategy to improve critical thinking skills is the use of the Inside Outside Circle learning model. The objectives of the study were (1) to examine how the Inner Outer Circle educational method influences students’ Analytical Reasoning related to colloid content, and (2) to gather students' opinions on the use of the Inside Outside Circle model in the context of colloid topics. This investigation used a quantitative method through a Quasi-experimental methods, particularly a design using a control group that is not equivalent. The method of sampling utilized was intentional sampling.The subjects of the study consisted of two groups: class XI IPA C functioned as the experimental group, whereas class XI IPA D served as the control group.The instruments utilized included lesson plans, student worksheets, assessment questions, and feedback surveys. Data collection involved a test for critical thinking abilities, which consisted of 8 multiple-choice questions and 9 essay questions that were validated for reliability, achieving scores of 0. 628 and 0. 691, both indicating high reliability, in addition to a student response survey. For the data analysis, tests for homogeneity and normality were first carried out, followed by hypothesis tests using the Mann-Whitney technique, and the N-Gain test was then conducted. The results of the hypothesis test that was performed (1) The Mann-Whitney test indicates that 0,000 < 0. 05. This indicates that the Inside Outside Circle learning approach has an impact on students' critical thinking abilities, and (2) the average score of student responses to the inner outer circle educational method on analytical reasoning abilities in the experimental classroom is 81%. The group that underwent the experiment showed a rise with an average N-Gain of 0. 541, placing them in the moderate range. In contrast, the control group had an increase with an average N-Gain of 0. 228, which is considered low. This indicates that the educational activities in the group under study is successful in improving critical thinking abilities.